Reconstruction of Equivalent currents Using the Scalar Surface Integral Representation - Persson, Kristin; Gustafsson, Mats ; 0000-0003-4362-5716 (Technical Report LUTEDX/(TEAT-7131)/1-25/(2005), 2005)
Knowledge of the current distribution on a radome can be used to improve radome design, detect manufacturing errors, and to verify numerical simulations. In this paper, the transformation from near-field data to its equivalent current distribution on a surface of arbitrary material, i.e., the radome, is analyzed. The transformation is based on the scalar surface integral representation that relates the equivalent currents to the near-field data. The presence of axial symmetry enables usage of the fast Fourier transform (FFT) to reduce the computational complexity. Furthermore, the problem is regularized using the singular value decomposition (SVD). Both synthetic and measured data are used to verify the method. The quantity of data is large since the height of the radome corresponds to 29 − 43wavelengths in the frequency interval 8.0 − 12.0GHz. It is shown that the method gives an accurate description of the field radiated from an antenna, on a surface enclosing it. Moreover, disturbances introduced by copper plates attached to the radome surface, not localized in the measured near field, are focused and detectable in the equivalent currents. The method also enables us to determine the phase shift of the field due to the passage of the radome, cf. the insertion phase delay.
Published version: Electromagnetic Waves PIER 54, Ed. J.A. Kong, pp. 179-198, EMW Publishing, Cambridge, Massachusetts, USA, 2005.
Keywords: arbitrary geometric structures; surface integral equation; singular value decomposition; near field to equivalent currents transformation; radome applications